Pelatihan Penulisan Karya Tulis Ilmiah bagi Siswa Kelas XII Sekolah Menengah Agama Katolik (SMAK) Santa Maria Fatima Betun - Augusta De Jesus Magalhaes; Marselus E. N. Lebok; Yuditha Sosiana Kofi; Yuventus Tamelab; Damian Puling; Marianus Teti; Kristin Gladis Mauk; Mariyanti Novita Bisik (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
Scientific paper writing training at Santa Maria Fatima Betun Catholic High School (SMAK) in Betun City, Malaka Regency, East Nusa Tenggara, was conducted to enhance students’ literacy, understanding of scientific writing structure, and critical thinking skills. This program represents a community-based empowerment initiative aligned with the Merdeka Curriculum and supports the achievement of higher education Key Performance Indicators (IKU). The implementation involved needs analysis, socialization, intensive training, guidance in selecting writing topics, writing assistance, and monitoring and evaluation. The results indicate a significant improvement in students’ comprehension and skills in scientific writing. A total of 15 student papers are targeted for publication in national journals, accompanied by the development of a scientific writing strategy module. The program also increased students’ awareness of the importance of scientific writing in supporting academic achievement and future career competitiveness. Supporting outputs such as articles, posters, videos, and publication plans contribute to the sustainability of the program. Using a participatory approach, this activity proved relevant to the school’s Merdeka Curriculum through intracurricular learning. It is expected to serve as a model for literacy development and be replicated in other secondary schools in Malaka Regency.